SOCIAL-EMOTIONAL LEARNING PROGRAMS IN ELEMENTARY SCHOOLS: ENHANCING STUDENT COMPETENCIES AND ACADEMIC OUTCOMES - Romli, Faiz; Prima, Ellen; Dharin, Abu (STKIP Melawi, 2025)
Abstract: Elementary education has increasingly recognized social-emotional learning (SEL) as a vital pedagogical framework for promoting comprehensive student growth. SEL encompasses processes through which children acquire knowledge, attitudes, and skills to understand emotions, achieve goals, demonstrate empathy, maintain relationships, and make responsible decisions. This narrative literature review investigates contemporary evidence regarding SEL efficacy, influences on socioemotional capabilities and educational performance, and implementation factors in primary settings. A purposive review of 26 peer-reviewed articles spanning 2017-2025, focused on research from Scopus, ERIC, Google Scholar, and PubMed, synthesized findings thematically. Converging meta-analytic evidence indicates SEL programs positively influence social-emotional development across competency domains. Research documents positive associations between SEL participation and academic outcomes (effect sizes d = 0.17-0.35). However, effectiveness varies substantially based on implementation quality, teacher factors, organizational context, and student characteristics. Whole-school approaches show particular promise for sustainable impact. SEL represents valuable evidence-based strategy requiring adequate teacher preparation, ongoing professional development, organizational support, and contextual attention for successful implementation. Keywords: academic achievement, elementary school, implementation, program effectiveness, social-emotional learning Abstrak: Pendidikan dasar semakin mengakui pembelajaran sosial-emosional (SEL) sebagai kerangka pedagogis vital untuk pertumbuhan siswa komprehensif. SEL mencakup proses dimana anak memperoleh pengetahuan, sikap, dan keterampilan untuk memahami emosi, mencapai tujuan, menunjukkan empati, memelihara hubungan, dan membuat keputusan bertanggung jawab. Tinjauan literatur naratif ini menyelidiki bukti kontemporer mengenai kemanjuran SEL, pengaruhnya pada kemampuan sosioemosional dan kinerja pendidikan, serta faktor implementasi dalam lingkungan pendidikan dasar. Tinjauan purposif terhadap 26 artikel peer-review periode 2017-2025 dari Scopus, ERIC, Google Scholar, dan PubMed, mensintesis temuan secara tematik. Bukti meta-analitik konvergen menunjukkan program SEL mempengaruhi positif perkembangan sosial-emosional lintas domain kompetensi. Penelitian mendokumentasikan asosiasi positif antara partisipasi SEL dan hasil akademik (ukuran efek d = 0,17-0,35). Namun, efektivitas bervariasi substansial berdasarkan kualitas implementasi, faktor guru, konteks organisasi, dan karakteristik siswa. Pendekatan seluruh sekolah menunjukkan janji khusus untuk dampak berkelanjutan. SEL merupakan strategi berbasis bukti berharga yang memerlukan persiapan guru memadai, pengembangan profesional berkelanjutan, dukungan organisasi, dan perhatian kontekstual untuk implementasi sukses. Kata kunci: efektivitas program, implementasi, pembelajaran sosial-emosional, prestasi akademik, sekolah dasar